A Comparative Study of Seismic Behaviour of G+10 Storey Building with RCC and Composite Columns for Different Configurations - Swain, Sarmili; Parhi, P. K. (AMC Indian Journal of Civil Engineering, 2022)
In India, RCC structures are most commonly used as these are very much convenient for multistorey buildings. Steel concrete composite construction is not preferred because of its complexity in its analysis and design. It has unique characteristics of both the materials which results in greater economy and safety. In the present investigation, ETABS 2018 software is used for the analysis of a G+10 multistorey building of three different geometrical shapes of same plan area of 225m2. Comparison of seismic behaviour is done for all the three different plan areas consisting of RCC columns and composite columns. The various parameters considered in the study are storey displacement, storey drift, storey stiffness, and base shear. Comparison is done for four parameters for different cases and the best of the configuration is found out. Study of the above parameters is done by adopting response spectrum method for Zone III and Zone V.